1970
DOI: 10.1210/endo-87-2-233
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Biochemical Properties of Highly Purified HCG

Abstract: By a combination of Sephadex gel filtration, CM-C and DEAE-C chromatography, 2 highly purified HCG fractions (dA: 18,000 IU/mg, dB: 20,000 IU/mg) were obtained from a crude preparation (2130 IU/mg) which was extracted from the urine of normal pregnant women in the first trimester. They were characterized by histological response of the ovary of hypophysectomized immature rats, bioassay (the Steelman-Pohley method and the OAAD method), amino acid analysis and determination of carbohydrate content, and their hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1972
1972
1980
1980

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…It was formerly demonstrated that hCG with LH-like activity and hCFSH with FSHlike activity were isolated separately from lyophilized powder of trophoblastic tissue (Ashitaka, 1970;Tojo et al, 1973). Recently the biosynthesis in vitro of hCG from placenta was also confirmed using 3H-proline as a radioactive precursor .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was formerly demonstrated that hCG with LH-like activity and hCFSH with FSHlike activity were isolated separately from lyophilized powder of trophoblastic tissue (Ashitaka, 1970;Tojo et al, 1973). Recently the biosynthesis in vitro of hCG from placenta was also confirmed using 3H-proline as a radioactive precursor .…”
Section: Discussionmentioning
confidence: 99%
“…Up to this time, however, there has been no report which detected the presence of radioimmunological FSH activity in the medium of tissue culture of chorionic tissue although some workers have tried to assay chorionic FSH activity by radioimmunoassay for pituitary FSH (Benagiano et al, 1972). The chorionic FSH activity in the cultured medium should be detected by anti-hCFSH serum since hCFSH did not cross-react with anti-FSH serum of pituitary origin in Ouchterlony immunodiffusion (Ashitaka et al, 1970).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent demonstration (Ashitaka, 1970; Ashitaka, Tokura, Tane, Mochizuki & Tojo, 1970;Hamashige, Alexander, Abravanel & Astor, 1971;Ashitaka, Mochizuki & Tojo, 1972) that HCG extracted from placental tissue and urine has different bio¬ chemical characteristics, prompted us to study the conditions and the rate of incor¬ poration in vitro of [14C]L-leucine into human placental HCG with the purpose of investigating the biosynthesis and release of this hormone using such techniques as absorption with polymerized antisera, ion exchange chromatography, polyacrylamide gel electrophoresis and radioimmunoassay.…”
Section: Introductionmentioning
confidence: 99%
“…Isojima et al(1969) and Koyama (1971) also prepared two different fractions from HCG preparation and proved that one of them (Ag-1) showed biological activity and antigenicity of HCG, but the other (Ag-2) only showed the antigenicity of HCG. Later Ashitaka et al(1970) *:The antigenic activity of HCG was assayed by radioimmunoassay (Isojima et al, 1968) and expressed as IU HCG-equivalent by bioassay. **: Borate buffered saline (5 parts of 0 .1M borate buffer (pH8.6) mixed with 95 parts of 0.9% saline).…”
mentioning
confidence: 99%